PENDAMPINGAN ANALISIS BIAYA PRODUKSI TAHU PADA UNIT PENGOLAHAN HASIL (UPH) ERO MATE’NE KABUPATEN TAKALAR - Muh Tahir; Sri Argo Pradanto; Rizka Aulia Safarni (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2026)
The aimed of this community service activity is to evaluate the tofu production process and determine the production cost and profitability of the Ero Mate'ne Processing Unit (UPH) in Takalar Regency. The activity was conducted from May 20–26, 2026 through field observations, identification of cost components, measurement of production resources, and economic analysis. The results indicated that the total annual production cost reached IDR 2,407,264,750, consisting of fixed costs of IDR 32,666,250 and variable costs of IDR 2,374,598,500. With a production capacity of 3,000 soybean sacks per year, equivalent to 54,000 tofu molds, the production cost was calculated at IDR 44,579 per mold. At a selling price of IDR 50,000 per mold, annual revenue reached IDR 2,700,000,000, generating a profit of IDR 292,735,250 per year or approximately IDR 24,394,604 per month. The findings demonstrate that tofu processing at UPH Ero Mate'ne is economically feasible and profitable, as indicated by a Benefit-Cost Ratio (BCR) of 1.12. Improvements in raw material management, energy utilization, and product distribution efficiency could further enhance business performance and sustainability.